The role of family in improving the management of diabetes mellitus patients - Anita Lontaan; Yulien Adam; Femmy Keintjem; Sumiyati Sumiyati (Edukasi Ilmiah Indonesia, 2024)
Introduction: diabetes mellitus is a chronic disease that requires long-term management involving patients and their families. The role of the family in improving the management of diabetes mellitus patients is very important to achieve good blood sugar control and prevent long-term complications. This study aims at the role of family in improving the management of diabetes mellitus patients. Methods: this research is a quantitative method with a quasi-experimental research design with a non-equivalent control group research design with a sample size of 20 respondents Results: shows that in the intervention group, most family roles have a good category where respondents have family roles are as many as 7 people (70%) and respondents who have poor family roles are as many as 3 people (30%). While in the control group, respondents who had poor family roles were as many as 8 people (80%) and respondents who had good family roles were as many as 2 people (20%). In the final measurement (Post-test) in the intervention group and the control group, p = 0, 028 or p < 0.05 means that there are differences in family roles in both groups in the final measurement (Post-test) Conclusions: the role of the family is very important in improving the management of diabetes mellitus patients. Family support and involvement in assisting patients in living a healthy diet, following the right medication regimen, and maintaining an active lifestyle can help achieve good blood sugar control and prevent long-term complications. Factors such as knowledge of diabetes, emotional support, and ability to manage diabetes-related situations also influence the family's role in the management of this condition. Therefore, education to families about diabetes, the psychological and practical support they provide to patients, as well as their involvement in healthy lifestyle changes are important things to note.